An improved microwave radiometer for measurements on the human body - Osterrieder, S.
The construction and performance of a 4 GHz-radiometer for measurements on the human body is presented. The radiometer measures the temperature and emissivity simultaneously and independent of each other. Experimental and theoretical results are given and the resolution of the radiometer is investigated.